Severe Late-Onset Neutropenia in a Pregnant Patient with Multiple Sclerosis after Ocrelizumab - Casey J. Fealko; Morgan N. Rolon-Newton; Marisa J.L. Aitken; Scott D. Gitlin (Case Reports in Neurology)
Introduction: Ocrelizumab is a recombinant humanized anti-CD20 monoclonal antibody used to treat multiple sclerosis. Late-onset neutropenia, absolute neutrophil count <1.5 × 109/L that develops >4 weeks after last drug administration, is a known adverse event associated with anti-CD20 monoclonal antibodies, including rituximab and ocrelizumab. Case Presentation: We present the case of a 27-year-old woman who developed severe late-onset neutropenia during her third trimester of pregnancy after treatment with ocrelizumab 6 months prior. Conclusion: Neurologists should be aware of this risk and consider additional hematologic monitoring for pregnant patients who received anti-CD20 therapy as therapies such as G-CSF are available to help prevent serious infections.